Low Turnover of Soil Bacterial rRNA at Low Temperatures - Schostag, Morten Dencker; Albers, Christian Nyrop; Jacobsen, Carsten Suhr; Priemé, Anders (Frontiers in Microbiology, 2020)
Ribosomal RNA (rRNA) is used widely to investigate potentially active microorganisms in environmental samples, including Arctic soil microorganisms and other microbial communities that are subjected to pronounced seasonal variation in temperature. This raises a question about the turnover of intracellular microbial rRNA at environmentally relevant temperatures. We analyzed the turnover at four different temperatures relevant to Arctic environments of RNA isolated from soil bacteria amended with 14C-labelled uridine. We found that the half-life of recently produced RNA increased from 5.6 days at 20 °C to 25 days at 5 °C, and 226 days at -4 °C, while no degradation was detected at -18 °C during a one-year period. We discuss the implications of the strong temperature dependency of rRNA turnover for interpretation of microbiome data based on rRNA isolated from environmental samples.